PENGARUH DISIPLIN BELAJAR DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MAN DI KOTA PADANG - Putri Rahmadhani; Agus Irianto; Armiati Armiati (Jurnal Ecogen, 2018)
This research is conducted to obtain (1) the influence of discipline learning to student achievement, (2) the influence of students confidence to the student achievement, (3) the influence of discipline learning and students confidence collectively to the student achievement.This research is ex post facto research. The population in this reseach is IPS students at 11th  grade of MAN in Padang with the amount is 352 students. The total of samples are determined by using Slovin formula and proportional random sampling. From this pattern, it is obtained 187 students as the samples of the reseacrh. The techniques of collecting data that used in this research are questionnaire and documentation. The instrument of validity test uses product moment and for reliability test uses coefficient alpha formula. Uji prasyarat are conducted with normality test, hetokedastisity test, and multicolonierity test. The technique that is used  for analyzing data is multiple regression analysis. Basen on this research, it is obtained that (1) the discipline learning  has positive and significant influence to the student achievement for IPS students at 11th grade of MAN in Padang (2) The students confidence influences positively and significantly to the student achievement for IPS students at 11th grade of MAN in Padang (3) The discipline learning and students confidence have positive and significant inluence to the student achievement for IPS students at 11th grade of MAN in PadangKeyword :Discipline learning, student confidence, student achievement